International Exhibition by Artists – University Teachers, Maribor, Slovenia, October 4th-14th, 2024 (University of Maribor Press, 2024)
In the framework of the INTERNATIONAL SCIENTIFIC AND ART CONFERENCE: Rethinking childhood III - Teaching for an inclusive, technologically competent and sustainable society (2024) a catalog of the exhibition was published. The catalog features reproductions of artworks by artists employed at various higher education institutions in Slovenia and abroad. The accompanying text titled ART AND SCIENCE: PARALLEL LINES, PROPAGATION, INTERWEAVING (For the exhibition "Play of Perspectives, Strategies, and Decisions") was prepared by Mojca Puncer, PhD.